Role of Connexin 43 in an Inflammatory Model for TMJ Hyperalgesia - Ahmed, Fabeeha; Rahman, Md.; Thompson, Randall; Bereiter, David A. (Frontiers in Pain Research, 2021)
Temporomandibular joint disorders (TMD) consist of a heterogeneous group of conditions that present with pain in temporomandibular joint (TMJ) region and muscles of mastication. This project assessed the role of connexin 43 (Cx43), a gap junction protein, in the trigeminal ganglion (TG) in an animal model for persistent inflammatory TMJ hyperalgesia. Experiments were performed in male and female rats to determine if sex differences influence the expression or function of Cx43 in persistent TMJ hyperalgesia. Intra-TMJ injection of Complete Freund’s Adjuvant (CFA) caused a significant increase in Cx43 expression in satellite glial cells (SGC) that surrounded TG neurons at 4 days and 10 days post-injection in ovariectomized (OvX) female rats and OvX females treated with estradiol (OvXE), while TG samples in males revealed only marginal increases. Intra-TG injection of interference RNA for Cx43 (siRNA Cx43) three days prior to recording, markedly reduced TMJ-evoked masseter muscle electromyographic (MMemg) activity in all CFA-inflamed rats, while activity in sham animals was not affected. Western blot analysis revealed significant decreases in Cx43 protein in TG samples of females and males 3 days after siRNA Cx43. Intra-TG injection of the mimetic peptide GAP19, which inhibits Cx43 hemichannel formation, greatly reduced TMJ-evoked MMemg activity in all CFA-treated groups, while activity in sham groups was not affected. These results revealed a persistent increase in Cx43 protein in the TG in a sex-dependent manner after TMJ inflammation. By contrast, intra-TG blockade of Cx43 by siRNA or by GAP19 significantly reduced TMJ-evoked MMemg activity in both males and females following TMJ inflammation. These results indicated that Cx43 was necessary for enhanced jaw muscle activity after TMJ inflammation in males and females, a result that could not be predicted on the basis of TG expression of Cx43 alone.